2013
DOI: 10.1097/mnm.0b013e32835f945f
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of examining hepatic functional volume using technetium-99m galactosyl serum albumin scintigraphy in hepatocellular carcinoma

Abstract: ObjectivesThe aim of the study was to clarify the clinical significance of single-photon emission computed tomography/computed tomography (SPECT/CT) imaging in terms of technetium-99m galactosyl human serum albumin ( 99m Tc-GSA) scintigraphy. To this end, we examined the relationship using data from surgical records of 67 patients with hepatocellular carcinoma who underwent hepatectomy. Materials and methodsLiver functional parameters or functional volume was estimated by 99m Tc-GSA scintigraphy and computed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…We demonstrated that for some patients with discrepancies and invasion to major vessels and patients undergoing PVE, we could obtain clinically good outcomes by applying functional volumetry. The relationship between the functional volumes and the conventional laboratory data was already reported in our previous reports (20,32), in which the functional volume was well correlated with other functional liver reserves or portal pressure but not with morphological CT volumetry in patients who underwent PVE. Thus, this useful method to aid in deciding operative indication should be spread worldwide.…”
Section: Discussionsupporting
confidence: 60%
“…We demonstrated that for some patients with discrepancies and invasion to major vessels and patients undergoing PVE, we could obtain clinically good outcomes by applying functional volumetry. The relationship between the functional volumes and the conventional laboratory data was already reported in our previous reports (20,32), in which the functional volume was well correlated with other functional liver reserves or portal pressure but not with morphological CT volumetry in patients who underwent PVE. Thus, this useful method to aid in deciding operative indication should be spread worldwide.…”
Section: Discussionsupporting
confidence: 60%
“…Liver cirrhosis was present in 74 (61.2%) patients. Most had good reserved liver function with CTP class A in 119 patients (98.3%) and with low median MELD score of 8.0 (range, [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. Median ICGR 15 and AFP level were 7.1% (range, 0-68.8%) and 13.7 ng/mL (range, 0.8-4.8 × 10 4 ng/mL), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…12,13 In addition, preoperative measurement of hepatic functional volume using technetium-99 mgalactosyl human serum albumin (99mTc-GSA) scintigraphy has been performed to predict PLF. 14,15 Recently, because of an improvement of magnetic resonance image (MRI) modality, it has been reported that quantitative measurement of liver function is possible with the liver-specific hepatocyte-directed MRI contrast agent, Gadoxetic acid (Primovist, Bayer-Schering, Berlin, Germany). [16][17][18] However, previous studies were limited because of small number of enrolled subjects, [16][17][18] retrospective database, 16,18 postoperative assessment, 17 or only enrollment of major resection with including patients with liver metastasis from colon cancer and excluding patients with liver cirrhosis.…”
Section: Introductionmentioning
confidence: 99%
“…Five studies reported historical comparisons on the outcome rate of LF and mortality in the period before and [16,20,25], whereas the historical comparisons on the use of [ 99m Tc]Tc-GSA did not result in a significant decrease in the number of liver failure cases in the period after implementation of [ 99m Tc]Tc-GSA liver scintigraphy [56,58].…”
Section: Historical Comparisonsmentioning
confidence: 99%